Free versus Pedicled Perforator Flaps for Lower Extremity Reconstruction: A Multicenter Comparison of Institutional Practices and Outcomes - Koh, Keith; Goh, Terence L.H.; Song, Christopher Tam; Suh, Hyun Suk; Rovito, Peter V.; Hong, Joon-Pio; Hallock, Geoffrey G. (Journal of Reconstructive Microsurgery, 2018)
Background Of all body regions, lower extremity wounds have been and remain the greatest challenge. Perforator free flaps have been accepted as a reasonable option to solve this dilemma but require the complexity of microsurgery. As a consequence, the possibility that pedicled perforator flaps could supplant even perforator free flaps has recently gained intense enthusiasm.Methods A retrospective investigation was undertaken to compare the validity for the use of perforator flaps of all types at three dissimilar institutions, that is, a university, a regional center, and a community hospital. All flaps performed in the 5-year period, 2011 to 2015, were included to allow at least 1-year follow-up before data analysis. A total of 433 free perforator flaps and 52 pedicled perforator flaps had been performed specifically for the lower extremity.Results Patient demographics, wound etiology, and comorbidities were similar for all institutions. Free flaps were more commonly needed after trauma and for chronic ulcers. Pedicled flaps were more likely an option after tumor excision. Large defects or those involving the foot were better served by free flaps. Overall success for free perforator flaps was 90.1% and for pedicled perforator flaps was 92.3%, with no significant difference noted (p = 0.606) between institutions. Peripheral vascular disease was the only significant comorbidity risk factor for both free and pedicled flap failure.Conclusion Perforator flaps in general have become a reasonable solution for soft tissue defects of the lower extremity. Following careful consideration of the etiology, dimensions, location, patient comorbidities, and presence of adequate perforators, a pedicled or free perforator flap could potentially be successful. Pedicled perforator flaps, if adequate healthy soft tissues remain adjacent to the defect, forecast a continuance of the evolution in seeking simplicity yet reliability by the best flap possible for soft tissue closure of the lower limb wound.
Keywords: perforator flaps; pedicled flaps; free flaps; lower extremity